Congregational Management of Ecological Disaster Relief: A Theological Study of Psalm 24:1 - Sasongko, Yakob Arfin T; Jonathans, Kornelius Rulli; Nugroho, Andreas Eko (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
Abstract:This study aims to explore a theo-pedagogical model of Christian learning based on the Israeli Shema as a foundational framework for contextual Christian education. The research seeks to identify how the core theological principles embedded in the Shema—particularly its emphasis on covenantal obedience, holistic devotion, and intergenerational transmission of faith—can inform learning practices that are more relevant to contemporary educational settings. Employing a qualitative descriptive method supported by an in-depth literature review, this study analyses biblical-theological interpretations of the Shema alongside recent scholarly discussions in Christian pedagogy. The findings reveal that the Shema provides a comprehensive learning paradigm that integrates cognitive, affective, and practical dimensions of faith formation, emphasising the unity of belief, daily practice, and community life. The novelty of this study lies in its systematic integration of the Shema’s theological structure with contextual Christian education, offering a fresh framework that bridges ancient Israelite pedagogy and modern learning needs. The study’s implications highlight the urgency for Christian educators to adopt relational, life-oriented, and community-based learning approaches that foster deep spiritual formation and nurture holistic Christian identity within diverse and evolving educational contexts.